Fresh Pomegranate Juice Decreases Fasting Serum Erythropoietin in Patients with Type 2 Diabetes - Saleem A. Banihani; Shuaibu M. Shuaibu; Belal A. Al-Husein; Seham S. Makahleh (International Journal of Food Science)
Pomegranate juice (PJ) has been recognized to have various biological benefits in several pathological conditions. One such benefit is the augmentation of hemoglobin level and the number of erythrocytes in the human body. Here, we assessed the short-term effect of fresh PJ on the level of Erythropoietin (EPO) in patients with type 2 diabetes (T2D) compared to healthy individuals. Blood samples from 59 participants with T2D and 30 healthy individuals were collected after a 12-hour fast and 3 hours after administration of fresh PJ at 1.5 mL per kg body weight. Serum glucose was measured by standard method and commercially available chemiluminescent immunoassay kits were used to determine serum EPO concentration. Mean changes in serum EPO levels 3 hours after ingesting PJ and before the juice ingestion (EPO response to PJ) for both diabetic and healthy participants were -2.002 ± 0.541 vs. - 0.041 ± 0.214, respectively (P = 0.0087). This EPO response to PJ was found not to be correlated with age (P = 0.6622) and gender (P = 0.5354) for patients with T2D, while a negative correlation (P = 0.0183) between EPO response to PJ and fasting serum glucose concentrations was observed in these patients. In conclusion, fresh PJ reduced serum EPO level in patients with T2D, but not in healthy individuals, 3 hours after ingesting the juice. The EPO response to PJ was found to be negatively correlated with fasting serum glucose, but not with age and gender, of patients with T2D. This trial is registered with ClinicalTrials.gov Identifier. NCT03902288.